NILAI PENDIDIKAN KARAKTER DALAM FILM HABIBIE DAN AINUN 3 - Khotima, Khusnul; Saleh, Muhammad; Baharman, Baharman (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to: (1) Describe the reinforcement of religious character education values in the film Habibie & Ainun 3; (2) Describe the reinforcement of nationalism character education values in the film Habibie & Ainun 3; (3) Describe the reinforcement of independent character education values in the film Habibie & Ainun 3; (4) Describe the reinforcement of cooperative values in the film Habibie & Ainun 3; (5) Describe the reinforcement of integrity character education values in the film Habibie & Ainun 3. This research uses a descriptive qualitative approach. Data collection techniques in this study used observation and note-taking techniques. The data analysis techniques in this research are data reduction, presentation, and conclusion drawing. Data validity checking uses triangulation theory. The results of this study show the characteristics of reinforcing character education values in the film Habibie & Ainun 3, namely the reinforcement of religious values, nationalism values, independence values, cooperative values, and integrity values.